2004
DOI: 10.1038/ng1472
|View full text |Cite|
|
Sign up to set email alerts
|

A transcriptomic analysis of the phylum Nematoda

Abstract: The phylum Nematoda occupies a huge range of ecological niches, from free-living microbivores to human parasites. We analyzed the genomic biology of the phylum using 265,494 expressed-sequence tag sequences, corresponding to 93,645 putative genes, from 30 species, including 28 parasites. From 35% to 70% of each species' genes had significant similarity to proteins from the model nematode Caenorhabditis elegans. More than half of the putative genes were unique to the phylum, and 23% were unique to the species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
185
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 41 publications
10
185
2
Order By: Relevance
“…These ASP-like molecules were also specific for O. ostertagi and T. circumcincta and seem to have diverged early in the evolution of the nematode ASPs. These observations are in agreement with the results from Parkinson et al (2004) who showed that genes containing the SCP/Tpx-1/Ag5/PR-1/Sc7 domain have undergone lineage-specific amplification and divergence within the Strongyloidea. The function of ASP molecules in parasitic nematodes is still unclear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These ASP-like molecules were also specific for O. ostertagi and T. circumcincta and seem to have diverged early in the evolution of the nematode ASPs. These observations are in agreement with the results from Parkinson et al (2004) who showed that genes containing the SCP/Tpx-1/Ag5/PR-1/Sc7 domain have undergone lineage-specific amplification and divergence within the Strongyloidea. The function of ASP molecules in parasitic nematodes is still unclear.…”
Section: Discussionsupporting
confidence: 93%
“…The ASP protein family seems to be one of the largest nematode-specific protein families (Parkinson et al, 2004). In C. elegans, 36 ASP-like sequences have been found, 23 of them showing significant homology to the Ostertagia ASPs (WORMBASE).…”
Section: Discussionmentioning
confidence: 99%
“…Organization of its mitochondrial genome more closely resembles that of coelomate metazoans than that of its presumed closest relatives, the secernentean nematodes (1). In addition, T. spiralis (Dorylaimia) shares a similar proportion (45%) of its ESTs with the nematode Caenorhabditis elegans (Rhabditina) as it does with the fruit fly Drosophila melanogaster (Arthropoda: Drosophilidae) (2). Thus, many ESTs common to T. spiralis and C. elegans are not necessarily specific to nematodes but may be conserved among diverse taxonomic groups of invertebrates.…”
mentioning
confidence: 99%
“…For the B. xylophilus data set, the 672 contigs with taxonomy classification were further annotated, with seven assigned to bacteria and 665 assigned to eukaryota (Table 5). (Parkinson et al, 2004;Lilley et al, 2005).…”
Section: Taxonomic Classificationmentioning
confidence: 99%